Gregory of Nyssa: Homilies on the Our Father. An English Translation with Commentary and Supporting Studies : Proceedings of the 14th International Colloquium on Gregory of Nyssa (Paris, 4-7 September 2018) - Cassin, Matthieu; Grelier-Deneux, Hélène; Vinel, Françoise (Vigiliae Christianae, Supplements, 2021)
Gregory of Nyssa's Homilies on the Our Father are the second explanation of this central prayer of Christian worship in Greek Antiquity. Composed at the end of the 4th century, these five homilies offer a spiritual and pastoral commentary of the Pater Noster. The present volume, edited by Matthieu Cassin (Paris), Hélène Grelier-Deneux (Paris) and Françoise Vinel (Strasbourg), offers introductory materials, a new English translation, the first edition of the 15th century Latin translation by Athanasios Chalkeopoulos, together with five studies that form a commentary for the different homilies, and nineteen shorter contributions on various aspects of the text. The contributors envisage the text according to exegesis and theology, but also to philosophy, rhetoric and history of Christian communities.